Semantics-oriented ontology matching techniques for job seeker's profiles and job's description [electronic resource] - Fuad Mire Hassan, 1983- (2012)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2012